Teacher Strategies in Instilling Sexual Boundary Values in Children in Kindergarten - Hanum Mulia Pramesti; Reni Pawestuti Ambari Sumanto (International Journal of Science and Environment (IJSE), 2026)
This research focuses on the strategies used by school teachers to introduce sexual boundaries to young children during classroom learning. This is driven by the rise in cases of child sexual abuse, while discussions about sexual boundaries are still considered taboo at home and at school, and lack appropriate understanding and strategies for communicating them to children. Therefore, this study aims to analyze the strategies used by teachers, supporting factors, and various obstacles faced by teachers in implementing strategies to introduce sexual boundaries to children. The research method used was descriptive qualitative research, with data collection techniques through interviews and observations. Data collection was conducted at a Kindergarten/Kindergarten in Gunungpati District from February 23 to March 6, 2026. The results of the study indicate that instilling sexual boundaries values in early childhood is positioned as an integral part of character education in kindergarten. In delivering sexual boundaries material, there are three strategic stages, namely: (1) giving warnings, (2) raising awareness, and (3) giving educational punishment. In addition, the use of visual media, symbols, songs, and daily habits have been proven to be relevant to the concrete thinking characteristics of early childhood. Teacher understanding and institutional support through school policies, the provision of facilities that support privacy, and the involvement of the school committee are important factors in ensuring the sustainability of the systematic implementation of sexual boundaries education. The obstacles faced by teachers in delivering sexual boundaries material to children are that many parents still consider this topic taboo and therefore do not fully support providing an understanding of sexual boundaries from an early age.